El estilo de la cerámica Casma del Intermedio Tardío - Bastiand Atto, María Soledad (2006)
This article presents the Casma Ceramic Style, defined through the typological analysis of ceramics from the «Cerro Sechin» archaeological site. This time I present the overall results from Sector C, since it is a significant sample, both qualitatively and quantitatively, with 58,127 fragments. Complete and semicomplete pots were also studied. In Sectors «A» and «B» only whole pots were analysed. This analysis was made under the framework of the Sechin Archaeological Project, sponsored by the Volkswagenwerk Foundation.